Identifikasi hidroquinon dalam lotion pemutih dengan metode kromatografi lapis tipis - Burdah Burdah; Ass-Siri Mirriyan Farsya; Ernita Silviana; Amelia Sari; Maria Irwani (Poltekkes Kemenkes Aceh, 2023)
Background: Cosmetics have been widely used to enhance the appearance and make it look more attractive. One of the most commonly used cosmetics is lotion. As science and technology progress, many lotions are introduced to the market. As pharmaceutical regulations require, not all lotion products are safe, effective, and of high quality. However, many losses are caused by whitening lotion products in circulation, one of which is the addition of hydroquinone, a whitening substance that can cause damage to the skin.Objectives: This study aims to identify the hydroquinone content contained in whitening lotion.Methods: Experimental research using the Thin Layer Chromatography (KLT) method to test lotions for hazardous ingredients. It was conducted at the Chemistry Laboratory of Poltekkes Kemenkes Aceh in June 2022. Materials are whitening hand body lotion available online and not branded as many as five samples—determination of criteria, namely, low prices, high demand, and instant results. The single variable used in this study determines the presence or absence of hydroquinone in lotion samples.Results: This study has shown that five whitening lotion samples are positive. Sample S4 contains hydroquinone with an Rf value of 0,55 (< 0,05). Meanwhile, samples S1, S2, S3, and S5 were negative for hydroquinone.Conclusion: Some lotions tested have met the requirements of BPOM regulations and are safe to use, but one lotion is unsafe to use because it contains high hydroquinone.